Power play the Bush presidency and the Constitution - Pfiffner ,James P. (Brookings Intstitution Press, 2008)
"Analyzes the Bush presidency?s efforts to expand executive power, putting them into constitutional and historical perspective. Explores the evolution of Anglo-American thinking about executive power and individual rights. Documents how the current administration has undermined the separation of powers and shows how these practices have imperiled the rule of law"--Provided by publisher